2020
DOI: 10.31234/osf.io/k8pds
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association of COVID-19 Misinformation with Face Mask Wearing and Social Distancing in a Nationally Representative US Sample

Abstract: Wide-spread misinformation about the COVID-19 pandemic has presented challenges for communicating public health recommendations. Should campaigns to promote protective behaviors focus on debunking misinformation or targeting behavior-specific beliefs? To address this question, we examine whether belief in COVID-19 misinformation is directly associated with two behaviors (face mask wearing and social distancing), and whether behavior-specific beliefs can account for this association and better predict behavior,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 28 publications
4
37
0
1
Order By: Relevance
“…Belief in COVID-19 conspiracy theories is associated with lower scientific 61 and analytical 10,13,23,36,61,[68][69][70][71] reasoning, and less correct knowledge but more false beliefs about COVID-19 61 . Similarly, low levels of education are frequently associated with belief in COVID-19 conspiracy theories 9,15,27,28 . Rather than following analytical reasoning, people believing in conspiracy theories seem to more follow their intuitions, as they are more likely to infer relationships between unrelated phenomena 13 and to endorse epistemically suspect beliefs 5,7,18,19,28,52,61 , while conspiracy belief is lower for those who engage in flexible and critical thinking and who question their own ideas 10,70 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Belief in COVID-19 conspiracy theories is associated with lower scientific 61 and analytical 10,13,23,36,61,[68][69][70][71] reasoning, and less correct knowledge but more false beliefs about COVID-19 61 . Similarly, low levels of education are frequently associated with belief in COVID-19 conspiracy theories 9,15,27,28 . Rather than following analytical reasoning, people believing in conspiracy theories seem to more follow their intuitions, as they are more likely to infer relationships between unrelated phenomena 13 and to endorse epistemically suspect beliefs 5,7,18,19,28,52,61 , while conspiracy belief is lower for those who engage in flexible and critical thinking and who question their own ideas 10,70 .…”
Section: Discussionmentioning
confidence: 99%
“…People who are white have been found to endorse COVID-19 conspiracy beliefs less often than other ethnic groups in the United Kingdom 5 , whereas a higher percentage of Black people than other ethnicities do endorse them in the United States 22 . Individuals with lower (vs. higher) income tend to hold stronger beliefs in COVID-19 conspiracy theories 9,15,24,27 , as do individuals with lower (vs. higher) levels of education 9,15,27,28 . This may, however, depend on the type of conspiracy theory.…”
Section: Individual Differencesmentioning
confidence: 97%
“…26 Future studies examining mask-wearing behavior should include data points about individual behavior beliefs, protective beliefs, beliefs about infectious diseases, and misinformation beliefs. 28 The findings showed that unmasked visitors and incorrectly masked visitors ranged from 2% to 5% and 9% to 18%, respectively, across different retail stores (Fig 2). Also, unmasked and incorrectly masked staff in the retail stores ranged from 5% to 11% and 8% to 16%, respectively (Fig 2).…”
Section: Discussionmentioning
confidence: 93%
“…26 Future studies examining mask-wearing behavior should include data points about individual behavior beliefs, protective beliefs, beliefs about infectious diseases, and misinformation beliefs. 28…”
Section: Discussionmentioning
confidence: 99%
“…During the Covid-19 pandemic, the U.S. Centers for Disease Control and Prevention has found that excess mortality exceeds the official Covid-19 mortality count (1), which may be due to underdiagnosed Covid-19 due to low test access, atypical Covid-19 presentation, reduced healthcare seeking for acute non-Covid-19 conditions (2), or etiologically nonspecific death reporting (3). Despite excess deaths, the infodemic accompanying Covid-19 included misinformation that Covid-19 mortality was exaggerated (4) (5), and belief in misinformation is cross-sectionally associated with adherence to Covid-19 prevention measures such as mask-wearing (6).…”
Section: Introductionmentioning
confidence: 99%